Epidemiology of two decades of invasive meningococcal disease in the Republic of Ireland: an analysis of national surveillance data on laboratory-confirmed cases from 1996 to 2016. (2019) - Bennett, D.; O'Lorcain, P.; Morgan, S.; Cotter, S.; Cafferkey, M.; Cunney, R.
Abstract: We examined the epidemiology of invasive meningococcal disease (IMD) in the Republic of Ireland (ROI) between epidemiological year (EY) 1996/1997 and EY2015/2016. Over the 20 EYs, 3707 cases were reported with annual incidence rates per 100 000 peaking at 11.6 in EY1999/2000, decreasing significantly to 1.5 in EY2015/2016. The highest disease burden was in infants and children <5, whereas adults aged ⩾65 years experienced the highest case fatality ratio (CFR) of 15.7% but over the study period the median annual CFR remained low (4.4%). Meningococcal serogroup B (menB) dominated (78%), followed by menC (17%), menW (1%) and menY (1%). The incidence of menC IMD declined significantly in all age groups after menC vaccine introduction in 2000. MenB incidence also declined over the 20 EYs with decreasing trends in all age groups under 65, including an almost 50% decrease in infants over the final four EYs. IMD incidence in the ROI has declined, partly attributable to menC vaccination success, coupled with a spontaneous decline in menB. However, recent gradual increases in non-menB IMD and the introduction of vaccines targeting menB demand continued detailed surveillance to accurately monitor trends and to assess vaccine impact.